Description of nine new species of phytoseiid mites (Acari: Mesostigmata) from Sikkim, a north eastern States of India - Kar, Anamika; Karmakar, Krishna (Zootaxa, 2022)
A rapid roving survey was done in the East Sikkim district of the state Sikkim with a target to explore phytoseiid fauna of the region. Nine species of phytoseiid mites namely Amblyseius lanceae sp. nov.; Amblyseiulella cancellatus sp. nov.; Amblyseiulella gangtokiensis sp. nov.; Euseius tubuliferus sp. nov.; Okiseius pahari sp. nov.; Paraamblyseius ranipoolensis sp. nov.; Phytoseius ferrum sp. nov.; Typhlodromus (Anthoseius) himaliniae sp. nov. Typhlodromus (Anthoseius) kanchanjanghai sp. nov. are described with proper illustrations in the present paper.